Overexpression of Ubiquitin-Specific Protease 2 (USP2) in the Heart Suppressed Pressure Overload-Induced Cardiac Remodeling - Junhui Xing; Pengcheng Li; Jin Hong; Mengyu Wang; Yuzhou Liu; Yueqiao Gao; Jianzeng Dong; Heping Gu; Ling Li (Hindawi Limited, 2020)
Ubiquitin-specific protease 2 (USP2) is an important member of the deubiquitination system. GEO dataset revealed that USP2 was downregulated in the hearts under pressure overload. However, the cardiomyocyte-specific function of USP2 in the setting of pressure overload is unknown. In the current study, a mouse model of pressure overload was induced by transverse aortic constriction (TAC, 2 weeks). Overexpression of USP2 in the heart was conducted by AAV9 infection. Changes in heart histology were detected by Masson's trichrome staining and hematoxylin-eosin staining (H&E). Echocardiography was used to assess cardiac function. The size of cardiomyocytes was examined by wheat germ agglutinin (WGA) staining. Cardiac oxidative stress was detected by dihydroethidine staining. Our results showed that USP2 was downregulated in the cardiomyocytes following 2 weeks of TAC. Overexpression of cardiac USP2 preserved ventricular function following 2 weeks of TAC. Overexpression of cardiac USP2 inhibited TAC-induced cardiac remodeling, by suppressing cardiac hypertrophy, inhibiting inflammatory responses and fibrosis, and attenuating oxidative stress. Our findings reveal a previously unrecognized role of USP2 in regulating pressure overload-induced cardiac remodeling.